2016
DOI: 10.1111/jth.13407
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic characteristics of lower limb venous compression ultrasonography in suspected pulmonary embolism: a meta‐analysis

Abstract: To cite this article: Da Costa Rodrigues J, Alzuphar S, Combescure C, Le Gal G, Perrier A. Diagnostic characteristics of lower limb venous compression ultrasonography in suspected pulmonary embolism: a meta-analysis. J Thromb Haemost 2016; 14: 1765-72. Essentials• Lower limb ultrasonography (CUS) could be useful in suspected pulmonary embolism (PE).• We performed a metaanalysis on the diagnostic characteristics of CUS in suspected PE.• With a sensitivity of 41%, proximal CUS would be positive in one of every 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…A positive proximal CUS result has a high positive predictive value for PE. The high diagnostic specificity (96%) along with a low sensitivity (41%) of CUS in this setting was shown by a recent meta-analysis [165,166]. CUS is a useful procedure in the diagnostic strategy of patients with CT contraindications.…”
Section: Compression Ultrasonographymentioning
confidence: 97%
“…A positive proximal CUS result has a high positive predictive value for PE. The high diagnostic specificity (96%) along with a low sensitivity (41%) of CUS in this setting was shown by a recent meta-analysis [165,166]. CUS is a useful procedure in the diagnostic strategy of patients with CT contraindications.…”
Section: Compression Ultrasonographymentioning
confidence: 97%
“…It may be used in patients with suspected PE. Indeed, the presence of a proximal DVT is highly predictive of PE, allowing to rule for the diagnosis of PE without further thoracic imaging : A recent systematic review of the performances of CUS for diagnosing PE reported a sensitivity of 41% (95% confidence interval [CI], 36–46%) and a specificity of 96% (95% CI, 94–98%) .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although the specificity of proximal CUS was very high (96%), the authors advised caution as most included studies did not rigorously confirm the presence of PE in patients with positive CUS. 48 The use of a composite reference standard is, however, not without practical challenges as it is based on consensus. Thus, if this consensus cannot be reached, the equivocal studies usually have to be excluded from analysis.…”
Section: Reference Standard In Pulmonary Embolism Imagingmentioning
confidence: 99%